LCA database creation - Andreas Ciroth; Claudia Di Noi; Salwa Burhan; Michael Srocka (Indonesian Life Cycle Assessment Network (ILCAN), 2019)
LCA studies require a high volume of data and their quality has a direct influence on the quality of the Life Cycle Inventory (LCI) and Life Cycle Assessment (LCA) study overall. The use of LCA databases enables users to (i) reduce time, efforts, and resources for data collection and (ii) reflect supply chains they have no direct control over. On the other side, it creates the need to align own modeling of the foreground LCA study with the modeling in the database. In recent years, countries worldwide have been more and more motivated in supporting LCA studies by providing national databases that reflect their economy, energy mix, and disposal technologies. This article aims to give insights on the main needs, requirements, and challenges for the creation of an LCA database, with a special focus on national, reference databases. First, the article defines the main characteristics of LCA datasets and discusses data collection approaches. Secondly, LCA databases are defined, and the creation of LCA databases from developed datasets is addressed, including the case of national LCA databases. Finally, the existence of tools that could ease the LCA dataset and database creation process is investigated, namely the LCA Collaboration Server and the LCA Data-Machine. It is important that countries willing to create a national database are supported, for example with capacity-building workshops, by actors with a long tradition in the field, which is of mutual benefit: Countries with a long tradition in LCA will benefit from interactions with newcomers, for instance by discussing together unsolved methodological and interoperability issues; newcomers do not need to start from scratch but can benefit from gained experiences. Creating databases that provide specific data for various parts of the world supports LCA methodology and application in general, and it is not the least a chance for local LCA communities to bring in innovation into LCA, and benefit from existing experiences at the same time.